Pelatihan Mind Mapping sebagai Sarana Mencatat Siswa Kelas 5 SD dalam melatih Critical Thinking - Latifa Rahmanita; Rahmah Hastuti (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
The increasing intensity of internet use during the pandemic has resulted in new habits among internet users. This makes it easy for students to accept the information circulating, whether it is true, just a rumor, or false (hoax). That's why students need to improve their critical thinking skills to deal with this using a mind mapping program. This research aims to provide an understanding of mind mapping to elementary school students as a forum for them to record lessons, as well as train them to use critical thinking skills in making mind maps. The method used is community service in the form of psychoeducation and training. The results of the service show that mind maps can be a means for students to record lesson material and can train their critical thinking skills. This is shown by the high percentage of students' critical thinking skills which are declared good, namely 87.9% with an average of 51.67 from 33 students.